Are selection criteria for healthy pregnancies responsible for the gap between fetal growth in the French national Elfe birth cohort and the Intergrowth‐21st fetal growth standards?. Issue 1 (28th November 2018) - Heude, Barbara; Le Guern, Morgane; Forhan, Anne; Scherdel, Pauline; Kadawathagedara, Manik; Dufourg, Marie‐Noëlle; Bois, Corinne; Cheminat, Marie; Goffinet, François; Botton, Jérémie; Charles, Marie‐Aline; Zeitlin, Jennifer
Abstract: Background: The Intergrowth‐21st (IG) project proposed prescriptive fetal growth standards for global use based on ultrasound measurements from a multicounty study of low‐risk pregnancies selected using strict criteria. We examined whether the IG standards are appropriate for fetal growth monitoring in France and whether potential differences could be due to IG criteria for "healthy" pregnancies. Method: We analysed data on femur length and abdominal circumference at the second and/or the third recommended ultrasound examination from 14 607 singleton pregnancies from the Elfe national birth cohort. We compared concordance of centile thresholds using the IG standards and current French references and used restricted cubic splines to plot z ‐scores by gestational age. A "healthy pregnancy" sub‐sample was created based on maternal and pregnancy selection criteria, as specified by IG. Results: Mean gestational age‐specific z ‐scores for femur length and abdominal circumference using French references fluctuated around 0 (−0.2 to 0.1), while those based on IG standards were higher (0.3‐0.8). Using IG standards, 2.5% and 5.2% of fetuses at the third ultrasound were <10th centile for femur length and abdominal circumference, respectively, and 31.5% and 16.7% were >90th. Only 34% of pregnancies fulfilled IG low‐risk criteria, but sub‐analyses yielded very similar results. Conclusion: Intergrowth standards differed from fetal biometric measures in France, including among low‐risk pregnancies selected to replicate IG's healthy pregnancy sample. These results challenge the project's assumption that careful constitution of a low‐risk population makes it possible to describe normative fetal growth across populations.